Sequential Patterns in Social Interaction States for Regulation in Collaborative Learning - Vuorenmaa, Eija; Järvelä, Sanna; Dindar, Muhterem; Järvenoja, Hanna (Small group research, 2023)
This study explored sequential patterns in social interaction states for group-level regulation of learning during collaborative learning. The participants were secondary school students (N = 92) performing collaborative physics tasks. The videotaped sessions were analyzed regarding participation, social interaction, and group-level regulation types of co- and socially shared regulation. The results show that group-level regulation emerged most frequently in social interaction state that included cognitive and socioemotional interaction and whole-group participation, which also led to and followed regulation most frequently. The findings highlight the role of joint participation in social interactions for regulation of learning in collaborative group settings.